L'archivio di tempo reale: come salvaguardare e divulgare la cultura della musica elettronica? - Giulia Sarno (Musica Docta, 2023)
The archive of the Tempo Reale center for music research, production and education, founded by Luciano Berio in 1987, is a heritage of great importance for the recent history of electronic music. This article describes the initiatives that have been taken to promote the archive, as well as some ongoing projects: in particular, it presents the methods and perspectives adopted with the aim of disseminating knowledge of the heritage and widening access to it, also involving the potential stakeholders of the archive. Based on this limited experience and on the notion of the “activation” of the heritage, some theoretical perspectives are outlined, questioning the possible participatory construction and transmission of an “electronic music culture”.